Advancement in the Development of Therapeutics Against Zika Virus Infection - Li, Kangchen; Ji, Qianting; Jiang, Shibo; Zhang, Naru (Frontiers in Cellular and Infection Microbiology, 2022)
Zika virus (ZIKV), a re-emerging arbovirus, causes teratogenic effects on the fetus and normal nerve functions, resulting in harmful autoimmune responses, which call for the development of therapeutics against ZIKV infection. In this review, we introduce the pathogenesis of ZIKV infection and summarize the advancement in the development of therapeutics against ZIKV infection. It provides guidance for the development of effective therapeutics against ZIKV infection.